Realistic Reference for Evaluation of Vehicle Safety Focusing on Pedestrian Head Protection Observed From Kinematic Reconstruction of Real-World Collisions - Li, Guibing; Liu, Jinming; Li, Kui; Zhao, Hui; Shi, Liangliang; Zhang, Shuai; Nie, Jin (Frontiers in Bioengineering and Biotechnology, 2021)
Head-to-vehicle contact boundary condition and criteria and corresponding thresholds of head injuries are crucial in evaluation of vehicle safety performance for pedestrian protection, which need constantly updated understanding of pedestrian head kinematic response and injury risk in real world collisions. Thus the purpose of the current study is to investigate the characteristics of pedestrian head-to-vehicle contact boundary condition and pedestrian AIS3+ (Abbreviated Injury Scale) head injury risk as functions of kinematic-based criteria, including HIC (Head Injury Criterion), HIP (Head Impact Power), GAMBIT (Generalized Acceleration Model for Brain Injury Threshold), RIC (Rotational Injury Criterion) and BrIC (Brain Injury Criteria), in real world collisions. To achieve this, 57 vehicle-to-pedestrian collision cases were employed and multi-body modeling approach was applied to reconstruct pedestrian kinematics in these real world collisions. The results show that: head-to-windscreen contacts are dominant in pedestrian collisions of the analysis sample, and head WAD (Wrap Around Distance) floats from 1.5m to 2.3m, with a mean value of 1.84m; 80% cases have a head linear contact velocity below 45km/h or an angular contact velocity less than 40rad/s; pedestrian head linear contact velocity is averagely 83%±23% of the vehicle impact velocity, while the head angular contact velocity (in rad/s) is averagely 75%±25% of the vehicle impact velocity in km/h; 77% cases have a head contact time in the range 50-140ms, and negative and positive linear correlations are observed for the relationship between pedestrian head contact time and WAD/height ratio and vehicle impact velocity, respectively; 70% cases have a head contact angle floats from 40° to 70°, with the average value of 53°; the pedestrian head contact angles on windscreen (average=48°) are significantly lower than those on bonnet (average=60°); the predicted thresholds of HIC, HIP , GAMBIT, RIC, BrIC2011 and BrIC2013 for an 50% probability of AIS3+ head injury risk are 1300, 60kW, 0.74, 1470×104, 0.56 and 0.57, respectively. The findings of the current work could provide realistic reference for evaluation of vehicle safety performance focusing on pedestrian protection.